Private philanthropic trends in academic libraries - Gonzalez, Luis J. (Chandos information professional series, 2013)
This book is written with the senior library administrator and the development officers of academic institutions in mind. Chapters provide a historical perspective of the funding trends of the private philanthropic foundations and corporate giving programs towards academic libraries during the first decade of the 21st century. Library fundraisers and library administrators are presented with the information needed to start the process of selecting which grant maker agencies to approach. Chapters discuss which grant-making philanthropic foundations and corporate-giving programs will be more receptive to grant monies to library projects, which types of library projects they will be more likely to fund, and how to approach these agencies in order to increase the possibilities of receiving grant awards from them.